Demographic correlates of nicotine dependence in psychiatric patients - Singh, Yogendra; Sisodia, Anil; Gaur, Anil; Agarwal, Vikrant (International Journal of Research in Medical Sciences, 2021)
Background: Tobacco and nicotine dependence has high prevalence in patients with psychiatric disorders. The present study was conducted to delineate demographic correlates of tobacco and nicotine dependence in psychiatric patients. Methods: 102 patients were sampled from Institute of Mental Health and Hospital, Agra. Fagerström Test for Nicotine Dependence for Smoking, Fagerström Test for Nicotine Dependence for Smokeless Tobacco, The Drug Abuse Screening Test (DAST), Alcohol Use Disorders Identification Test (AUDIT) were used along with a proforma for recording demographic and clinical details of the patients. Results: The results suggested that the severity of nicotine dependence in total sample was as Very Low in 2.9%, Low in 15.7%, medium in 42.2%, and High in 39.2%. The results of association between demographic variables and nicotine dependence suggested that there was statistically significant association between nicotine dependence and gender, place of residence, marital status, type of family, annual income, history of mental illness, History of substance use and duration of tobacco use. Conclusions: The medium and high level of nicotine dependence amount to 81.40% sample is of true concern which warrant for an active intervention for tobacco cessation programs in majority of the patients.